IMPROVING SEVENTH-GRADE STUDENTS' VOCABULARY MASTERY THROUGH UNO GAME CARDS: CLASSROOM ACTION RESEARCH - Selvia Irawan; Norasiah Norasiah; Ari Andre Rianyansa; Basinun Basinun (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
In this study, students of MTs Muhammadiyah Gedongtengen Yogyakarta experienced difficulties in mastering English vocabulary. Students also feel bored in the language learning process. Since they are usually given tedious tasks such as writing and memorizing vocabulary, students are not actively involved in the learning process. The Uno game cards as an English language learning medium are essential in improving students' vocabulary mastery. It can help bridge the communication gap between teacher and students by helping teacher explain concepts better. This study aimed to investigate the effectiveness of Uno game cards in improving seventh-grade students' vocabulary mastery. This study adopted a Classroom Action Research (CAR) design following the Kemmis and McTaggart framework. The research was conducted in two cycles, each comprising four stages: planning, action, observation, and reflection. The participants were the teacher (collaborator) and the seventh grade of MTs Muhammadiyah Gedongtengen Yogyakarta, Indonesia. The participants were all students of Class VII at MTs Muhammadiyah Gedongtengen, Yogyakarta. The class consisted of 11 students, including 5 males and 6 females. The researcher involved all students in the class because Classroom Action Research focuses on solving instructional problems in a particular classroom setting. This CAR was conducted in two cycles, and the data collection technique was an observation, field notes, interview, and vocabulary test. Qualitative data were analyzed using the Miles, Huberman, and Saldaña interactive model, while quantitative data from vocabulary tests were analyzed using descriptive statistics. The findings indicated that Uno game cards effectively enhanced students’ vocabulary mastery and classroom engagement. Qualitative data showed increased student participation and motivation during the learning process, while quantitative results demonstrated a steady improvement in vocabulary achievement, with mean scores increasing from 62.18 in the pre-cycle to 74.91 in Cycle 1 and 78.91 in Cycle 2. These findings suggest that Uno game cards are an effective medium for supporting vocabulary learning among seventh-grade students. Thus, there were approximately 16.73 points of improvement during the cycles. Therefore, Uno game cards were found to be effective in improving seventh-grade students' vocabulary mastery and learning engagement.